A clinical study of cutaneous adverse drug reactions - Shah, Riddhi; Agrawal, Sakshi; Bhuptani, Neela (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Adverse cutaneous drug reactions pose a diagnostic challenge due to a myriad of clinical manifestations and wide variety of causative agents. Present study aims to record various clinical patterns of adverse drug reactions, their causative agents and to study the pattern of morbidity and mortality in patients with severe cutaneous adverse drug reactions. Methods: 150 patients with adverse cutaneous drug reactions were included who came to Department of Dermatology, Venereology and Leprosy at PDU Govt. Medical College and Hospital, Rajkot, Gujarat from September 2009 to September 2011. Thorough history with all routine haematological and biochemical investigations, septic screening were done. HIV testing was done in severe reactions. Appropriate specific treatment was given with counselling regarding the offending drug. Results: The most common age group was 21-30 years (26.67%) with male to female ratio being 0.92:1. Morbilliform rash was the most common clinical type (42.67%) in both HIV reactive and non-reactive patients. Antimicrobials were the most common group (29.33%) and nevirapine was the most common offending drug (27.33%). Mortality rate was 2% (3 out of 150 cases) and all the patients were of toxic epidermal necrolysis. Conclusions: The pattern of cutaneous adverse drug reactions and the causative drugs are remarkably different in our study. Knowledge of the pattern and the causative agent helps in better management and reduced consequences in these patients particularly in severe adverse cutaneous drug reactions.